The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/nu10101428
|View full text |Cite
|
Sign up to set email alerts
|

Addictive Eating and Its Relation to Physical Activity and Sleep Behavior

Abstract: The obesity epidemic has led to the exploration of factors contributing to its etiology. Addictive eating, physical activity, and sleep behaviors have all been independently associated with obesity, and recent research suggests plausible interrelationships between food addiction, physical activity, and sleep. This study aims to investigate the relationship between food addiction with physical activity and sleep behavior. Australian adults were invited to complete an online survey which collected information in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 71 publications
2
38
0
Order By: Relevance
“…On the other, the relevance of healthy living habits, such as physical exercise directed at intrinsic goals and good eating behavior should be underlined, because of their effects on physical and emotional health of workers and the work environment [5,4]. Therefore, organizations, following the recommendations of the HERO model, should design programs designed to promote the health of their employees, focused on making workers aware of the importance of physical exercise and a balanced diet [21,36]. They should also give workshops on psychological strategies for effective emotional regulation [39,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other, the relevance of healthy living habits, such as physical exercise directed at intrinsic goals and good eating behavior should be underlined, because of their effects on physical and emotional health of workers and the work environment [5,4]. Therefore, organizations, following the recommendations of the HERO model, should design programs designed to promote the health of their employees, focused on making workers aware of the importance of physical exercise and a balanced diet [21,36]. They should also give workshops on psychological strategies for effective emotional regulation [39,37].…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled eating consists of excessive consumption of food in response to external signals from the environment, characterized by subjective increase in appetite and absence of self-control of eating behavior [33,34]. It negatively affects wellbeing and has been related with such health problems as obesity [35,36]. In this line, it has been demonstrated that ineffective emotional regulation strategies have a key role in starting and maintaining such eating behavior [37].…”
Section: Introductionmentioning
confidence: 99%
“…Most nursing professionals showed poor sleep quality (60%), which could be the result of working in rotating shifts and high job stress [24][25]. The results also showed that poor sleep quality negatively influenced self-esteem [BPSQI=-1.36 p<.001], suggesting that inadequate sleep reduces the tendency to think positively and is related to negative emotional states which affect the emotional and psychological wellbeing of nurses [28].…”
Section: Discussionmentioning
confidence: 99%
“…One question related to health and satisfaction of nursing professionals has to do with inadequate sleep, which could result from different factors, such as working rotating shifts and high levels of stress [24][25]. A sleep deficit, whether in amount or duration, negatively influences an individual's physical and psychological health, socioemotional functioning and psychosocial adjustment [26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation